GARNET-CLINOPYROXENE BAROMETRY OF CRUSTAL AND MANTLE ASSEMBLAGES: IMPLICATION FOR THE ESTIMATION OF DIAMOND POTENTIAL - Simakov S.K. (My University, 2007)
Determination of the depth of crustal and mantle xenoliths is an urgent issue. The xenoliths are potential carriers of diamonds and subdivided into three types by composition: ultramafic, eclogite, and pyroxenite (intermediate between the two former types). Eclogites contain omphacitic clinopyroxene, while peridotites contain Cr-diopsides. This study is aimed at development of a universal garnet–clinopyroxene barometer for estimating pressure in both mantle and crustal rocks. The PT parameters can be estimated using the known effect of variation in the content of the tschermakite end member (CaAl2SiO6) in clinopyroxene with growth in pressure.